Effect of Distance on the Maximum Data Transfer for Different Mounting Elevations of XBee Pro Module in Viral Advertisement System - Mohd Rusdy , Yaacob; Nik Anwar, Nik Syahrim; Nordin, Nurdiana; Muhammad, Mohd Nazrin (Trans Tech Publications, 2013)
This paper presents a study on the effect of distance between XBee Pro modules to the maximum data transfer for three different mounting elevations. The study has been conducted by using two units of XBee Pro modules which each represents a receiver and a transmitter. The transmitter is mounted in three different elevations which are 0.5, 1.5 and 2.5 meter from the ground while the receiver is fixed at the same elevation. When the transmitter continuously transmits the wireless signal carrying its particular address, the receiver will detect the signal address once the range of communication of both receiver and transmitter intersects. The results obtained are the values of data size, in bytes, with respect to the distance between receiver and transmitter for different mounting elevations of transmitter. These data are then converted into graph that illustrates the data size-distance characteristics for each mounting elevation. Finally, the best mounting elevation is to be identified based on the result obtained.